Characterization of Soybean Kapi During Fermentation with Bacillus spp. - Wittanalai S. (2014)
The changes in enzymatic activities, aroma profiles, color development, phenolic content (including isoflavones), and radical scavenging properties during fermentation to produce soybean kapi condiment using two isolates of Bacillus subtilis IS4 (IS4) and B. amyloliquefaciens RY1 (RY1) are reported. The activities of three hydrolytic enzymes (β-glucosidase, α-amylase, and protease) from both strains showed similar change patterns; the highest activities were observed during days 2-4 of fermentation. With respect to volatile compound formation, the common dominant volatile compounds found in both IS4 and RY1 fermented samples were aldehydes and N-containing compounds. However, IS4 also contained acids and esters as dominant compounds, while RY1 also contained alcohols as dominant compounds. Moreover, the change of Hunter color (increase in a*- and b*- value and decrease in L*-value) appeared to be coincidental with the development of browning and the increase in fluorescence intensity in all samples of IS4 and RY1. In addition, the fermented samples had significant increase (P<0.05) of phenolic content as well as DPPH radical scavenging activity, which was well correlated. Although the content of glucoside isoflavone (daidzin and genistin) and aglycone isoflavone (daidzein and genistein) increased in the early stage of fermentation and dramatically decreased thereafter in both strains, their derivatives may possess antioxidant activity. These results show the potential of the individual B. subtilis strains IS4 and B. amyloliquefaciens RY1 as functional starter cultures for the enrichment of the antioxidant and free-radical scavenging activity in soybean kapi. © 2012 Copyright Taylor and Francis Group, LLC.